Harnessing Indigenous Forage Legume Species to Bridge Feeding Gaps and Mitigate Climate Change Impacts - Louhaichi, Mounir; Hassan, Sawsan; Zoghlami, Aziza (Alliance Bioversity International-International Center for Tropical Agriculture, 2023)
Sulla (Hedysarum spp.) emerges as a noteworthy legume, renowned for its resilience in semi-arid agricultural settings. With traits like high productivity, deep roots, and palatability, it offers a compelling solution for agricultural sustainability. Diverse species of sulla, showcasing varied drought-tolerance traits, allow for tailored selection to meet specific needs in varying environmental conditions. This legume contributes to soil fertility, erosion control, and provides high-protein forage, making it an ideal choice for livestock, promoting methane reduction and increased productivity. Despite Tunisia's genetic biodiversity, limited forage legume utilization persists. The poster highlights an innovative approach, promoting local native forage legume species for resilience, engaging farmers through participatory strategies, and emphasizing the importance of well-adapted, drought-tolerant fodder for mitigating climate change impacts. The outcomes include identification of indigenous forage species suitable for drought-prone areas, improved livelihoods, enhanced ecosystem services, and increased farmers' adoption. The next steps involve targeted breeding programs, investigating environmental factors' impact on forage quality, assessing maturity stage influence, scaling successful technologies, and strengthening seed production systems.